Online Intrusion and Security Measures in Social Networking Environment – A Survey - Rani S, Jamuna; Vagdevi, S (International Journal of Computer Sciences and Engineering, 2020)
Social networking has become the topmost application among users to share and communicate information. With the advancement in communication and smartphone capabilities increasing number of users are connected to social network. News items, memes and marketing campaigns are all hosted on social network. Enterprises are also using social network to reach to more customer bases. The popular online social networking platforms such as Twitter, Facebook, Instagram etc. have attracted public helping them connected to family, friends, and relatives. People share videos, texts, pictures, and some confidential information knowingly or unknowingly through these sites and thus, OSNs have become the main source of targets for cyber attackers. Cyberattacks have been increasing for the last few decades throwing a serious threat to the internet world. Security of personal data on social network user is important. In this survey, the various methods of intrusion of social networks for gaining access to private information and the countermeasures are studied. The goal of study is to identify open issues, so that a more secure solution can be designed to solve the problem and discuss about various OSN threats such as misuse of identity, malware, phishing attacks etc. and recommends some of the threat’s preventive measures.